IMPACT ENERGY DISSIPATOR WITH VARIABLE STIFFNESS AND DRY FRICTION LAYERS - Domínguez Gurría, Miguel Alberto; Estrada Barbosa, Quirino; Szwedowicz, Dariusz; Martinez, Eladio (2022)
This paper presents an experimental and numerical study that allows to evaluate the dissipation of impact energy, proposing a friction damper with the use of layers (LFD) for impact energy dissipation. The study is carried out on a macro scale of contact between the layers and friction elements. The effects of displacement and applied speed are experimentally analyzed. Numerically, the FEM analyses the effects of the preload and the material of the friction layers on the hysteretic behavior of the LFD. The energy dissipation in a cycle increases with respect to the applied displacement. The operating range of the LFD is variable, because the stiffness of the system increases with respect to the applied displacement. The preload applied to the damper varies with respect to the displacement applied. A theoretical approach is established to estimate the energy dissipation of the system with previously defined parameters or, to define the geometry and material of the damper elements for an estimated energy range.